The spacesuit film a history, 1918-1969 - Westfahl, Gary (McFarland & Co., 2012)
"This critical history comprehensively examines science fiction films that portray space travel realistically by having characters wear spacesuits. It discusses classics; innumerable films which gesture toward realism but betray that goal with melodramatic villains, low comedy, or improbably monsters; the distinctive spacesuit films of Western Europe, Russia and Japan; and America's televised Apollo 11 moon landing (1969)"--Provided by publisher.